(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Autores: Susana De Tomás Morales (Dir.), Cristina Amich Elías (Coord.), Gracia Abad Quintanal, Alberto Priego Moreno y Ana- Pilar Velázquez Ortiz. Editorial: Dykinson, Madrid, 2013. 280 páginas.